QEOSA: A Pedagogical Model That Harnesses Cultural Resources to Foster Creative Problem-Solving - Dai, David Yun; Cheng, Huai; Yang, Panpan (Frontiers in Psychology, 2019)
The nature of creative cognition is complex and multi-faceted, often involving thinking processes and dispositions modulated by implicit cultural beliefs systems and ways of thinking. In this article, we build on existing research on the relations of creative cognition and culture, and explore how specific cultural resources can be harnessed to foster creative problem solving in education. We first review the recent changes in our understanding of creative thinking, from an exclusive focus on divergent thinking to a more inclusive view of creative problem solving as socially negotiated and culturally modulated, carrying important cultural functions. We then explore the issue of how cultural resources, particularly indigenous epistemologies (i.e., culture-specific ways of thinking about the world), can be harnessed to foster creative thinking in education, and what developmental and pedagogical issues are involved. To further illustrate how this can be done with young children, we introduce QEOSA, a pedagogical model inspired by Chinese philosophy and in keeping with the current creativity research; we discuss the viability and efficacy of this model with tangible student outcomes and findings of experimental research, and further argue that transfer of creative problem solving does occur when interventions are carefully designed with specific pedagogical features. We finally conclude this article by indicating the value of this line of work that integrates psychological, cultural, and educational principles in fostering the development of a creative mindset with relevant knowledge, skills, dispositions, and values.